2018
DOI: 10.1097/sla.0000000000002017
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF Therapy Is Associated With an Increased Risk of Postoperative Morbidity After Surgery for Ileocolonic Crohn Disease

Abstract: Preoperative anti-TNF therapy is associated with a higher risk of morbidity after surgery for ileocolonic CD. This information should be considered in the surgical management of these patients, particularly with regard to the preoperative preparation and indication of temporary defunctioning stoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 34 publications
2
94
2
2
Order By: Relevance
“…Data demonstrate that patients undergoing surgery for UC in the biologic era are more likely to undergo a staged procedure, postoperative complications and readmissions [23][24][25]. The French Groupe d'Etude Th erapeutique des Affections Inflammatoires du Tube Digestif has made similar findings regarding the surgery for ileocolonic Crohn's disease [26]. These data suggest that surgery for UC should be avoided within 6 weeks of biologic therapy if possible and a staged approach used after emergency colectomy for acute disease where biologic rescue therapy has been administered.…”
Section: Discussionmentioning
confidence: 93%
“…Data demonstrate that patients undergoing surgery for UC in the biologic era are more likely to undergo a staged procedure, postoperative complications and readmissions [23][24][25]. The French Groupe d'Etude Th erapeutique des Affections Inflammatoires du Tube Digestif has made similar findings regarding the surgery for ileocolonic Crohn's disease [26]. These data suggest that surgery for UC should be avoided within 6 weeks of biologic therapy if possible and a staged approach used after emergency colectomy for acute disease where biologic rescue therapy has been administered.…”
Section: Discussionmentioning
confidence: 93%
“…Whilst immunosuppressive therapy is effective, it undoubtedly has an impact on outcome for those that eventually need surgery [18]. Studies from both the USA and France have indicated increased postoperative morbidity and readmission rates in IBD patients needing surgery whilst on biological therapy [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of biological therapy on postoperative morbidity is now recognized. Although some studies [19][20][21][22][23] did not find any correlation between the use of infliximab and the occurrence of early septic complications after abdominal surgery for CD, several retrospective studies [24][25][26], meta-analyses [27][28][29] and a recent large, prospective, multi-institutional series [30] have reported a significant association between the preoperative use of biological therapy and postoperative intra-abdominal septic complications. In consideration of the deleterious effect on postoperative morbidity caused by biological therapy, refinement in surgical techniques may very well be needed to maintain or improve postoperative rates of morbidity.…”
Section: Discussionmentioning
confidence: 99%